Modeling of dynamic properties of national economic systems - Toroptsev, Yevgeniy; Korolev, Vitaliy; Chernova, Olga; Matveeva, Lyudmil (Serbian Journal of Management, 2018)
The objective of the article is to develop the modeling of dynamic properties of national economic systems at different hierarchic levels from the universal statistical and mathematical perspective of the economic system dynamics modeling theory. Taking into account the suggested model, the major factors in the economic development of the present-day Russia have been studied in the article. The methodology of socio-economic analysis has been applied to assess the impact of the identified factors on quantitative and qualitative indicators of the Russian economy development. The article describes the role of the analysis of national economy dynamic properties in increasing the efficiency of the national economy development strategies management in order to achieve structural and dynamic harmonization of innovative processes and economic growth.
Keywords: Models; экономика; ЭКОНОМИЧЕСКИХ СИСТЕМ; динамические свойства